Interdisciplinary Curriculum Designing in Higher Education - Jamal Salimi; Hasan Maleki (Interdisciplinary Studies in the Humanities, 2012)
The theoretical basis of interdisciplinary curriculum is found in progressive educational philosophy. The progressive movement is an approach to learning that places great emphasis on creativity, active learning, "naturalistic" learning, real world outcomes, and experience. The other more recent theoretical basis for interdisciplinary curriculum is found in constructivism theory. Constructivism is a theory of learning that states that each person must construct his or her own reality. The constructivism principle states that experience is the key to meaningful learning, not someone else's experience abstracted and condensed into textbook form, but it is based on one's own direct experience. In the interdisciplinary curriculum, the debates about themes or content development will refuse any disciplinary classification. The content will define on exist problems and this problem must to have a bases in reality. The essential and real problems of life will be a basic that must to use not only in design of curriculum bout also in the process of teaching. In the other hand, the curriculum has core elements that have not correct structure without them. In this article, we try to reviewing the literature of interdisciplinary curriculum in higher education and in other section, we will determine core element of higher education interdisciplinary curriculum and practical guideline to design an interdisciplinary curriculum.